2001
DOI: 10.4141/p00-005
|View full text |Cite
|
Sign up to set email alerts
|

Genotype–environment interaction of no-till winter wheat in Western Canada

Abstract: . 2001. Genotype-environment interaction of no-till winter wheat in Western Canada. Can. J. Plant Sci. 81: 7-16. Differences among cultivars in their response to changes in crop water availability are reflected in genotype-environment (GE) interactions for grain yield. With the recent expansion of the winter wheat production area in western Canada, it is important that plant breeders and agronomists have an understanding of the significance of GE interactions as they relate to regional adaptation of genotypes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Significant interactions between genotypes and environments for peanut yield and yield components have been reported . Domitruk et al (2001) indicated that the analysis of variance procedure is a useful tool for estimating the existence and magnitude of G × E interactions. This assessment is the primary basis for identifying the best performers and their range of adaptability, both temporally and spatially.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Significant interactions between genotypes and environments for peanut yield and yield components have been reported . Domitruk et al (2001) indicated that the analysis of variance procedure is a useful tool for estimating the existence and magnitude of G × E interactions. This assessment is the primary basis for identifying the best performers and their range of adaptability, both temporally and spatially.…”
mentioning
confidence: 99%
“…Considering yield stability in conjunction with mean yield may provide a more appropriate comparison of genotypes than when using only mean yield (Kang, 1993). Domitruk et al (2001) indicated that the analysis of variance procedure is a useful tool for estimating the existence and magnitude of G × E interactions. By evaluating the performance of different peanut cultivars in multiple environments, new cultivars adapted to these environments can be identified.…”
mentioning
confidence: 99%
“…These cultivars were grown in 17 field trials that were located throughout Saskatchewan from 1989 to 1991 (Table 1). Details on the performance of the cultivars and the soil type of the trial locations have been reported in a related publication (Domitruk et al 2001). For personal use only.…”
Section: Methodsmentioning
confidence: 99%
“…Rapid early season growth results in prolifi c tillering and a large proportion of the total biomass is normally accumulated by heading (Darroch and Fowler, 1990). Because no-till winter wheat often exhausts most of its available soil water reserves by heading (Domitruk et al, 2001), evaporation during the 2-wk period immediately before heading, root zone extractable soil water at heading, and evaporation during the last 2 wk in July are the primary weather factors determining grain yield (Entz and Fowler, 1989). Unpredictable growing season moisture and temperature means that the crop is often subjected to both intermittent and terminal drought (Domitruk et al, 2000).…”
Section: Straw Strength and Rust Resistancementioning
confidence: 99%